Safety and Efficacy of Immune Checkpoint Inhibitors for Patients With Metastatic Urothelial Carcinoma and End-Stage Renal Disease: Experiences From Real-World Practice - Kuo, Ming-Chun; Su, Po-Jung; Huang, Chun-Chieh; Luo, Hao-Lun; Chiu, Tai-Jan; Li, Shau-Hsuan; Wu, Chia-Che; Liu, Ting-Ting; Cheng, Yuan-Tso; Kang, Chih-Hsiung; Su, Yu-Li (Frontiers in Oncology, 2020)
Background: Immune checkpoint inhibitors (ICIs) are used widely for treating metastatic urothelial carcinoma (mUC). In practical settings, evidence is lacking on the efficacy of ICIs in some difficult-to-treat patients, such as those with end-stage renal disease (ESRD). Herein, we evaluate the safety and efficacy of ICIs for patients with mUC and ESRD. Methods: For this retrospective study, patients with mUC who were given ICIs at Kaohsiung Chang Gang Memorial Hospital and Linkou Chang-Gung Memorial Hospital between April 2016 and November 2019 were consecutively enrolled. All clinicopathologic data, treatment responses, and adverse events were recorded. The immune-related adverse events (AEs), objective response rate (ORR), progression-free survival (PFS), and overall survival (OS) were compared between ESRD and non-ESRD groups. Results: In total, 129 patients with mUC were enrolled, with 11 patients categorized as the ESRD group. Among these patients with ESRD receiving ICIs, 7 of 11 (63.6%) had high-grade (grade ≥ 3) AEs, chiefly hematologic toxicity. Some rarely encountered AEs were noted, including toxic epidermal necrolysis, tuberculosis reactivation, ascites, and cytokine release syndrome. Patients in the ESRD group had numerically higher ORR (54.5% vs. 28.8%, p = 0.09), PFS (7.1 vs. 3.5 months, p = 0.42), and OS (not reached vs. 15.4 months) than the non-ESRD group. A multivariate Cox regression model demonstrated that leukocytosis (hazard ratio [HR]: 2.63; 95% confidence interval [CI]: 1.23–5.63; p = 0.01) and neutrophil-to-lymphocyte ratio (HR 2.91; 95% CI: 1.30–6.53; p = 0.01) were independent prognostic factors. Conclusion: Administration of ICIs in patients with mUC and ESRD demonstrated a modest antitumor activity, and should be used with caution for increasing risk of hematologic toxicity.